The debates of the Kharijites in the challenge of the caliphate of Imam Ali bin Abi Talib (peace be upon him) and his response to them: (a historical study) - Mohammed, Sahar Abdullah (Al-Adab Journal, 2021)
Following the SafinBattle in the year (37 AH), the major role of the Kharijites was emerged as an apostate group from the real Islamic religion during the succession of Imam Ali Peace Be Upon Him (PBUH). Because they went out of his obedience after the arbitration. When they saw that the caliphate is a right for all Muslims, there is no difference between Qureshi and others whether Arabic or Ajami.Besides, some other issues that are considered as controversy and disagreement.In this matter, they saw that fighting Imam Ali was holy duty which had to do. This was apparent during their mobilization to fight the Imam in the Nahrawan Battle, and his followers killed them the most murderous killers such as Abdullah bin Khbab and his wife. However, their differences with Imam Ali PBUH had roots and occasions before that time. Imam Ali PBUH responded in many debates on a number of issues that he discussed with them such as their disagreement with him about what took place in the Camel Battle and on the vision of the Imam in his leadership of the Safin Battle of against Muawiyah bin Abu Sufyan. Nonetheless, the Imam responded to this by refuting their arguments in front of people. This was directly through a discussion with them, or indirectly via sending a great companion: Abdullah Bin Abbas (May Allah be pleased with him) to them in order to change their previous opinions regarding the view towards the conduct of governance and state affairs in accordance with the Islamic perspective and other aspects. Those showed the truth that the Imam provided it and destroyed the falsehood that Kharijites called for.